Hepatitis B carriage and Brucella seroprevalence in urban and rural areas of Bolu province of Turkey: A prospective epidemiologic study - Oğuz KARABAY; Erdinç SERİN and Ali TAMER and Feray GÖKDOĞAN and Hacer ALPTEKER and Arzu ÖZCAN and Hüseyin GÜNDÜZ (Turkish Journal of Gastroenterology, 2019)
-